Literatura de auto-ajuda cristã: em busca da felicidade ainda na terra e não só para o céu - Bessa, Daniela Borja (2008)
The theme of this thesis is about Christian Self-Help Literature. The research was motivated by the following general objectives: to understand the presuppositions of self-help genre; to identify a possible relationship between Secular Self-help Literature and Christian Self-Help Literature; to verify a role of Self-Help Literature among Protestant Christians. The study of Christian Self-help Literature was elected because it is a genre in expansion since 1980s as a relevant segment of evangelical publishing market. From American writers, such literature has linked religious and psychological discourse by using biblical verses and psychological technical terms from Transpersonal, Humanist and Positive Psychology and also it has achieved great respectability among Evangelical Christians. The hypothesis that supported its investigation is that Christian Self-Help Literature is received by Christians as a welcome initiative once it links psychological and religious discourse and it contributes to humanization of its readers as instrument which promotes emotional and spiritual health. In order to verify such hypothesis, the thesis was divided in two major blocks or parts. In the first block, social and psychological influences which have impacted Self- Help literature are analyzed. In the second block, the Christian Self-help is analyzed. As it was intended by this thesis, to verify what has provoked such Christian Self-Help Literature on its Christian readers, a research was carried with Evangelical Christians from Belo Horizonte and neibouring cities. The books with more indications in the research were analyzed in the final chapter. It could be perceived that Christian Self-Help Literature, in opposite way to Secular Self-Help Literature, which is seen as prejudicial and abusive, was considered as contributive to personal growth and spiritual development. In other words, the research has pointed out a positive role of Christian Self-Help Literature as a perception of evangelical community